Relationships among plasma granzyme B level, pruritus and dermatitis in patients with atopic dermatitis. Issue 3 (December 2016) - Kamata, Yayoi; Kimura, Utako; Matsuda, Hironori; Tengara, Suhandy; Kamo, Atsuko; Umehara, Yoshie; Iizumi, Kyoichi; Kawasaki, Hiroaki; Suga, Yasushi; Ogawa, Hideoki; Tominaga, Mitsutoshi; Takamori, Kenji
Highlights: Plasma granzyme (Gzm) B level increased in atopic dermatitis (AD) patients. Plasma GzmB level correlated with severity of dermatitis including pruritus in AD. Plasma GzmB level uncorrelated with severity of itch and dermatitis in psoriasis. Abstract: Background: A topic dermatitis (AD) is a multifactorial inflammatory skin disease characterized by skin barrier dysfunction, allergic inflammation and intractable pruritus resistant to conventional antipruritic treatments, including H1 -antihistamines. Granzymes (Gzms) are a family of serine proteases expressed by cytotoxic T lymphocytes and natural killer cells that have been shown to modulate inflammation. However, the relationship between Gzms and pathology in AD remains unclear. Objective: This study assessed the correlation between plasma GzmB levels and severity of pruritus and dermatitis, in AD patients. Methods: Plasma was collected from 46 patients with AD, 24 patients with psoriasis, and 30 healthy controls. AD severity was assessed with the scoring atopic dermatitis (SCORAD) index, psoriasis severity with the psoriasis area and severity index (PASI), and degree of pruritus by visual analogue scale (VAS) score. GzmA, GzmB and gastrin releasing peptide (GRP) levels were measured by enzyme-linked immunosorbent assays. Results: Plasma GzmB concentrations were significantly higher in patients with AD and psoriasis than in healthy controls. Correlation analyses showed that plasma GzmB concentrations positively correlated with SCORAD and serum levels of severity markers such as thymus and activation-regulated chemokine, and lactate dehydrogenase in AD patients. Moreover, plasma levels of GRP, an itch-related peptide, were higher in patients with AD, positively correlating with VAS score and plasma GzmB level. In addition, plasma GzmB concentration was significantly lower in the treatment group than the untreated group with AD. Meanwhile, there were no correlations among GzmB levels, VAS score and PASI score in patients with psoriasis. In contrast to the results of plasma GzmB, plasma GzmA levels were unchanged among AD, psoriasis and healthy groups, and showed no correlations with VAS score and SCORAD index in patients with AD. Conclusion: Plasma GzmB levels may reflect the degree of pruritus and dermatitis in patients with AD.